Figure 6 in Somatic musculature of Tardigrada: phylogenetic signal and metameric patterns - Marchioro, Trevor; Rebecchi, Lorena; Cesari, Michele; Hansen, Jesper Guldberg; Viotti, Giulia; Guidetti, Roberto (Zenodo, 2013)
Figure 6. Schematic representations of musculature. A, Echiniscus testudo; B, Milnesium cf. tardigradum; C, Acutuncus antarcticus. Muscles of the ventral group are in red, their nodes are marked by hexagons; muscles of the lateral group are in blue, their attachment points and nodes are marked by squares; muscles of the dorsal group are in green, their attachment points and nodes are marked by circles. Letters and numbers identify the muscle attachment points (see text). Ph, pharynx. Published as part of Marchioro, Trevor, Rebecchi, Lorena, Cesari, Michele, Hansen, Jesper Guldberg, Viotti, Giulia & Guidetti, Roberto, 2013, Somatic musculature of Tardigrada: phylogenetic signal and metameric patterns, pp. 580-603 in Zoological Journal of the Linnean Society 169 (3) on page 589, DOI:10.1111/zoj.12079, http://zenodo.org/record/5291175